Basivertebral Nerve Ablation - Huang, Junjian; Delijani, Kevin; Jones, Jesse; Di Capua, John; El Khudari, Husamuddin; Gunn, Andrew J.; Hirsch, Joshua A. (Seminars in Interventional Radiology, 2022)
Low back pain is one of the most prevalent musculoskeletal ailments in the United States. Intraosseous radiofrequency ablation of the basivertebral nerve is an effective and durable therapy for low back pain and can be offered to patients who have chronic low back pain of greater than 6 months of duration, failure to respond to noninvasive therapies for 6 months, with either Modic Type I or Type II changes at L3–S1. This article reviews the anatomy and physiology, patient selection, technique, and evidence regarding basivertebral nerve ablation.
Keywords: interventional radiology; pain management; basivertebral nerve; nerve ablation